2007
DOI: 10.1074/jbc.m611779200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Roles of Leptin in Osteogenic Stimulation in Thoracic Ligament Flavum Cells

Abstract: Obesity is a risk factor for thoracic ossification of ligament flavum (TOLF) that is characterized by ectopic bone formation in the spinal ligaments. Hyperleptinemia is a common feature of obese people, and leptin, an adipocyte-derived cytokine with proliferative and osteogenic effects in several cell types, is believed to be an important factor in the pathogenesis of TOLF. However, how leptin might stimulate cell osteogenic differentiation in TOLF is not totally understood. We reported here that leptin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 49 publications
0
65
0
Order By: Relevance
“…Recent studies have demonstrated that the activation of MAPK signaling cascade contributes to osteogenic differentiation of cultured LFCs induced by mechanical stress and leptin, which were considered as the causes of OLF [25,43]. However, whether the activation of ERK1/2 and p38 MAPK is involved in rhGDF-5 induced LFCs differentiation need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the activation of MAPK signaling cascade contributes to osteogenic differentiation of cultured LFCs induced by mechanical stress and leptin, which were considered as the causes of OLF [25,43]. However, whether the activation of ERK1/2 and p38 MAPK is involved in rhGDF-5 induced LFCs differentiation need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…), 100 U/ml penicillin and 100 pg/ml streptomycin, and incubated in 95% air/5% CO 2 atmosphere at 37 °C, LFCs were harvested with 0.2% trypsin (Sigma-Aldrich)/0.02% ethylenediamine tetraacetic acid once they migrated from the explants and became confluent. The third passage LFCs were used in the following studies [25].…”
Section: Lfcs Cultures and Treatmentmentioning
confidence: 99%
“…To date, a few in vitro studies have revealed the mechanisms by which leptin induces osteogenic differentiation in spinal ligament cells [6,24]. Fan et al [6] demonstrated that leptin caused significant increases in mRNA expression of alkaline phosphatase (ALP) and osteocalcin in thoracic ossification of ligament flavum (TOLF) cells, but not in non-TOLF cells, and that the effect was both dose-and time-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al [6] demonstrated that leptin caused significant increases in mRNA expression of alkaline phosphatase (ALP) and osteocalcin in thoracic ossification of ligament flavum (TOLF) cells, but not in non-TOLF cells, and that the effect was both dose-and time-dependent. These findings suggest that TOLF cells are considerably more sensitive to leptin stimulation and that leptin has the potential to promote osteogenic differentiation in ligament flavum cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results show that blocking of SDF-1/CXCR4 signaling only had an effect on phosphorylation of STAT3 at the early stage of osteogenic differentiation in MC3T3-E1 cells. Furthermore, STAT3 and Runx2 are two of the major transcription factors that play essential roles in osteogenesis, they interact with each other in the nucleus, and Runx2 is a master regulator at the early phase of osteogenic differentiation; this interaction might affect osteogenic regulation (33)(34)(35). Further studies are needed to explain whether the interplay of STAT3 and Runx2 are involved in STAT3 signaling at the early stage of osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%